2014
DOI: 10.1073/pnas.1318408111
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase 3B regulates duration of neural crest production via repression of Sox10

Abstract: Neural crest stem cells arise within the central nervous system but then undergo an epithelial-to-mesenchymal transition to migrate away and contribute to the peripheral nervous system and craniofacial skeleton. Here we show that DNA methyltransferase 3B (DNMT3B) is responsible for the loss of competence of dorsal neural tube cells to generate emigrating neural crest cells. DNMT3B knockdown results in up-regulation of neural crest markers, prolonged neural crest emigration, and subsequent precocious neuronal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…For example, Sox10 expression is regulated by both DNA methylation and histone methylation. DNMT3B binds to and methylates the promoter of Sox10 to regulate the duration of NC production (Hu, Strobl-Mazzulla, Simoes-Costa, et al, 2014). Conversely, histone demethylase KDM4A (JMJD2A), removes the H3K9me3 repressive mark at the promoters of Sox10 as well as several other NC specifiers (e.g., Snai2 , FoxD3 , Sox8 ) during NC specification (Matsukawa, Miwata, Asashima, & Michiue, 2015; Strobl-Mazzulla et al, 2010).…”
Section: | the Putative Nc Grnmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sox10 expression is regulated by both DNA methylation and histone methylation. DNMT3B binds to and methylates the promoter of Sox10 to regulate the duration of NC production (Hu, Strobl-Mazzulla, Simoes-Costa, et al, 2014). Conversely, histone demethylase KDM4A (JMJD2A), removes the H3K9me3 repressive mark at the promoters of Sox10 as well as several other NC specifiers (e.g., Snai2 , FoxD3 , Sox8 ) during NC specification (Matsukawa, Miwata, Asashima, & Michiue, 2015; Strobl-Mazzulla et al, 2010).…”
Section: | the Putative Nc Grnmentioning
confidence: 99%
“…Access to the enhancers and promoters of NC genes is tightly regulated by a host of epigenetic modifiers in vivo and in vitro during the formation of NC cells (Rada-Iglesias et al, 2012). Multiple NC-related genes in chicken such as, Sox10 (Hu, Strobl-Mazzulla, Simoes-Costa, Sanchez-Vasquez, & Bronner, 2014; Jacques-Fricke & Gammill, 2014), Sox9 , Foxd3 , and Snai2 (Strobl-Mazzulla, Sauka-Spengler, & Bronner-Fraser, 2010), Sox2 and Sox3 (Hu, Strobl-Mazzulla, Sauka-Spengler, & Bronner, 2012), and Pax3 in mouse (Wei & Loeken, 2014), have been identified as targets of transcriptional control. At the chromatin level, recent studies in frog have shown that the Polycomb Repressive Complex (PRC) interacts with SNAI1/2 proteins to control the levels of histone H3K27 trimethylation on target promoters, which allows NC-promoting genes to be expressed (Tien et al, 2015).…”
Section: | the Putative Nc Grnmentioning
confidence: 99%
See 1 more Smart Citation
“…DSGs were regulated by MXE, RI and SE in Brc8.5-vs-Brc10.5, and regulated by MXE, RI, SE and A3SS in Brc8.5-vs-Brc9.5 and Brc9.5-vs-Brc10.5 comparison. Among 29 DSGs, Ngrn, Ddr1, Dctn1, Dnmt3b, Ect2, Map2, Mbnl1, Meis2, Vcan and App were related with nervous system development (57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Furthermore, Dnmt3b, a NTD candidate gene, was regulated by SE during neural tube development (67,68).…”
Section: Discussionmentioning
confidence: 98%
“…What is more, some studies [10] have reported that myelination of SCs can be regulated by DNA methylation process. Although previous studies [15, 16] have provided some clues for understanding the relationship between DNA methylation and gene regulation of SCs, due to the limitation of experimental technique, the mechanisms driving all of this still are not understood very well. In this study, for the first time, we comprehensively characterized the differences of genomewide DNA methylation expression regarding SCs before and after PNS injury by Methylated DNA Immunoprecipitation Sequencing (MeDIP-Seq).…”
Section: Introductionmentioning
confidence: 99%